Analysis of risk factors for early neurological deterioration after intravenous thrombolysis in patients with acute ischemic stroke - Fang, Jungang; Sun, Hui; Lu, Xinyu (Frontiers in Neurology, 2025)
ObjectiveThe aim of this study is to examine the potential risk factors contributing to early neurological deterioration (END) following intravenous thrombolysis in patients diagnosed with acute ischemic stroke (AIS).MethodsClinical data was gathered from AIS patients who underwent intravenous thrombolysis at the Affiliated People’s Hospital of Jiangsu University between January 2020 and December 2023. Patients were subsequently categorized into two groups based on the occurrence of END within 24 h post-thrombolysis: the END group and the non-END group. A comparative analysis of the clinical data from both groups was conducted. The application of Multivariate Logistic regression facilitated the identification of independent risk factors and the construction of a nomogram prediction model.ResultsThe study encompassed a total of 249 AIS patients, with 32 patients (12.9%) developing END. The multivariate analysis revealed that NIHSS Score immediately after thrombolysis (p < 0.001), the Trial of Org 10172 in Acute Stroke Treatment (TOAST) typing of large artery atherosclerosis (p = 0.025), and a prior history of diabetes (p = 0.023) were independent risk factors for the development of END post-thrombolysis. A nomogram was constructed to generate the ROC curve, and the AUC value was 0.809 (95% CI, 0.732–0.885).ConclusionThis nomogram, which demonstrates good discrimination and high predictive value, identifies NIHSS score immediately after thrombolysis, TOAST classification of large artery atherosclerosis, and a history of diabetes as independent risk factors for early neurological deterioration (END) in acute ischemic stroke (AIS) patients receiving intravenous thrombolysis.